SYNTHETIC COVALENTLY COMBINED DERIVATIVES OF 2H-1-BENZOPYRAN-2-ONE - A. Z. Abyshev; C. B. Nguyen (Разработка и регистрация лекарственных средств)
Coumarins (also known as 2Н-1-benzopyran-2-one or 2H-chromen-2-one), in contrast to other groups of heterocyclic compounds, are of many different structures. They constitute an important class of pharmacological agents possessing a range of different physiological activities including anti-cancer, anti-oxidant, anti-inflammation, anti-HIV, anticoagulant, anti-bacterial, analgesic, comparative immune-modulation. Recently, coumarins have attracted intense research interest in various fields of science. Of great interest is the possibility that many substances from this class of heterocyclic compounds could be a source of the development of highly active drugs for the therapy of several diseases. Many of these agents are combined (hybrid) molecules, which are designed through concept of molecular hybridization and have shown multiple pharmacological activities. This review will focus on recent advances in the molecular and cellular mechanisms of the action of the combined coumarin derivatives involved in the relationship between the«structure and activity» ((SAR) of these highly interesting heterocyclic compounds.